Copper(II) complexes of fused ring selenosemicarbazones: Synthesis, structure elucidation, biological activity and molecular modeling. (15th March 2023) - Malhi, Rinku; Singh, Iqubal; Carmieli, Raanan; Savci, Ahmet; Sharma, Rekha
Graphical abstract: Abstract: Reaction of copper(II) acetate with cyclohexanoneselenosemicarbazone (Hcysesc), 5-chloro isatinselenosemicarbazone (5-ClHIstsesc), 1-methyl isatinselenosemicarbazone (1-MeHIstsesc), 3-indole selenosemicarbazone (3-HInsesc), 3-acetylindole selenosemicarbazone (3-AcHInsesc and 2-naphthaldehyde selenosemicarbazone (2-Hnaphsesc) in 1:2 (M: L) molar ratio yielded complexes of stiochiometry, [Cu(L)2 ] 1 –6 (L = cysesc 1 ; 5-ClIstsesc 2 ; 1-MeIstsesc 3 ; 3-Insesc 4 ; 3-AcInsesc 5 ; 2-naphsesc 6 ). All the complexes are characterized by IR, Mass and ESR spectroscopy. Two well defined g values (g‖ and g⊥ ) in ESR spectrum of complexes 1 –4, 6 indicate axial symmetry, whereas symmetry around copper(II) metal in complex 5 is confirmed by three different g values (g1, 2.095; g2, 2.15; g3, 2.26), which supports rhombic distortion. The value of g‖ obtained is greater than g⊥, which is greater than ge, in 1 –4, 6 is in well agreement in dx2-y2 ground term of square planar geometry. The value of empirical factor f for complexes 1 –4, 6 lies in the range, 102–135 cm indicating a square planar geometry with small distortion, where as in complex 5 value ( f = 146 cm) is in conformity of tetrahedral geometry with larger distortion. All the compounds (selenosemicabazones and their complexes) are tested for DPPH radical scavenging, ABTS radical scavenging, FRAP ferric reducing and CUPRAC cupric reducing antioxidant capacity assay and all the compounds have shown good antioxidant capacity in general. Best results are obtained for H 1 L with FRAP, 6.75 ± 0.01 μg TE/ml and CUPRAC, 9.52 ± 0.07 μg TE/ml. All the compounds are also tested for their anti-tubercular activity against M. tuberculosis H37RV strain ATCC27294. Ligands, H 1 L, H 3 L, H 6 L and complex 6 have shown highest anti-TB activity (MIC = 1.6 µg/ml) which is similar to the standard drugs (Isoniazid, Ethambutol). anti-TB activity of H 2 L and H 5 L (MIC = 12.5 µg/ml and 25 µg/ml) increased on complexation with copper(II) (MIC = 1.6 µg/ml, 2 ; 12.5 µg/ml, 6 ). Experimental results are supported by molecular modeling studies, where a considerable intermolecular interaction of these compounds with the active site of amino acid of enoyl reductase from M. tuberculosis has been observed with minimum binding energy −6.2, −7.3, −7.7, −7.4, −7.2, −8.7 Kcal/mol for H 1 L, H 2 L, H 3 L, H 4 L, H 5 L, and H 6 L and −7.2, −9.4, −8.6, −9.3, −9.9, and −10.6 Kcal/mol for copper complexes 1, 2, 3, 4, 5 and 6 exhibited respectively.